Development of an Informative Poster on German Folk Festivals as a Cultural Learning Media - Fatimah Hanim; Muhammad Alif D. Egon; Surya Masriani Hutagalung; Margaretha Febriyanti Manurung (EDUCATION JOURNAL OF INDONESIA, 2024)
The study discusses the development of an informative poster on German folk festivals as a cultural learning medium. Using a qualitative descriptive approach with a development research design based on the stages of Richey and Klein, the authors explore the topic with detailed constraints on the types of folk festivals available in Germany. The data sources used include references from the internet, books, and other supporting materials. The result of this study is the creation of a product in the form of an informative poster about German festivals, categorized into five types: Oktoberfest, Karneval, Fasching or Fastnacht (costume parties), the Berlin Film Festival, and the World’s Largest Wine Festival: Wurstmarkt. Keywords: Development, Informative Poster, German Folk Festivals.